Hypericin mediated photodynamic therapy induces ferroptosis via inhibiting the AKT/mTORC1/GPX4 axis in cholangiocarcinoma - Wei An; Kai Zhang; Guangbing Li; Shunzhen Zheng; Yukun Cao; Jun Liu (Translational Oncology)
Cholangiocarcinoma remains a challenging primary hepatobiliary malignancy with dismal prognosis. Photodynamic therapy (PDT),a less invasive treatment, has been found to inhibit the proliferation and induce ferroptosis, apoptosis and necrosis in other tumor cells in recent years. Regrettably, the role and exact molecule mechanism of PDT is still incompletely clear in cholangiocarcinoma cells. Ferroptosis is a novel regulated cell death(RCD), which is controlled by glutathione peroxidase4(GPX4) with the characteristics of iron dependent and excessive intracellular accumulation of lipid peroxides. This novel form of RCD has attracted great attention as a potential new target in clinical oncology during recent years. In this study, we observed that hypericin mediated PDT(HY-PDT) could significantly inhibit the proliferation of the cholangiocarcinoma cells and suppress migration and the epithelial mesenchymal transition (EMT) as well. Then, we conducted transcriptome sequencing and bioinformatics analysis and observed that HY-PDT was most likely involved in ferroptosis, apoptosis, the EMT process and AKT/mTORC1 signaling pathways in cholangiocarcinoma cells. Next, a series of in vitro and in vivo experiments were performed to confirm that HY-PDT could trigger cholangiocarcinoma cells ferroptosis through inhibiting the expression of GPX4 protein. In terms of molecular mechanism, we found that HY-PDT induced ferroptosis by decreasing GPX4 expression via suppression of the AKT/mTORC1 signaling pathway. In addition, we also found that HY-PDT inhibit cholangiocarcinoma cells migration and the EMT process by inhibiting the AKT/mTORC1 pathway. Our study illustrated a new mechanism of action for HY-PDT and might throw light on the individualized precision therapy for cholangiocarcinoma patients.